Aggressive Behaviours among Pupils: Prevalence and Management in Ibadan North Local Government Area - Babalola, Abiodun Emmanuel (International Journal of Social Learning (IJSL), 2023)
This study investigated the prevalence and management of aggressive behavior in the North Ibadan Regional Government. This study used a phenomenological qualitative approach with a multi-stage sampling procedure using three elementary school teachers from each selected school, ten teachers as the sample. Teacher Management Strategy for Student Aggressive Behavior Interview Schedule (TMS_PABIS) as the qualitative data obtained were transcribed and summarized to provide a basis for interpretation and thematic analysis. The findings revealed kicking, hitting, snapping, throwing objects, screaming, and biting. It can be concluded that the aggressive behavior manifestations of the lower elementary school students are high because this requires proper management before they move to the upper elementary grades and other educational levels. It involves awareness of various strategies that can be used by teachers and other education stakeholders rather than focusing on a particular system, especially social skills.